Program Literasi Baca Tulis: Implementasinya dalam Meningkatkan Akhlak Siswa - Rofiq, Moh Ainur; Septian, Damar (Journal of Elementary Education Research, 2024)
This study aims to describe the implementation of the literacy programme as well as the supporting and inhibiting factors in improving the morals of fifth grade (V) students in MI. This type of research is field research with a descriptive qualitative approach. The data sources used are primary and secondary data. Data collection techniques through observation, interviews and documentation. The data validity test was carried out by means of observation and triangulation. The data analysis technique is by reducing data, presenting data, and verification. The results showed that students' morals are improved through the literacy programme with three stages: habituation, development and learning. The supporting factors of the literacy programme in improving students' morals are the natural environment, interesting moral reading books according to age, family environment, and self-awareness. The inhibiting factors of the literacy programme in improving students' morals are the family environment and self-awareness. The impact of this research is able to provide insight and reference regarding the learning of literacy reading and writing programmes that can be used as a means to improve the morals of grade V MI students. The implementation of the literacy programme in improving the morals of fifth grade students at MI Alam Alfa Kids is running well according to the desired goals.